LITERATURE REVIEW: ANALISIS PENERAPAN K3 DI PABRIK PERKEBUNAN KELAPA SAWIT - Rizki Khairunnisa; Susilawati (CV. ADIBA AISHA AMIRA, 2024)
The safe work safety or safety culture model in oil palm plantations is challenging because the workforce, especially field workers, have a lower level of education. This is especially because field workers often come into contact with chemicals, both pesticides and fertilizers, as well as sharp work tools such as machetes, hoes and dodos. Previous research has shown that the risk of work accidents due to OSH is not implemented. However, to fully understand this issue requires a thorough literary awareness. In this study, the application of OSH in palm oil mills will be thoroughly reviewed in the literature. In this study, data and findings from previous studies will be collected, examined and synthesized. The safe work safety or safety culture model in oil palm plantations is challenging because the workforce, especially field workers, have a lower level of education. This is especially because field workers often come into contact with chemicals, both pesticides and fertilizers, as well as sharp work tools such as machetes, hoes and dodos. Previous research has shown that the risk of work accidents due to OSH is not implemented. However, to fully understand this issue requires a thorough literary awareness. In this study, the application of OSH in palm oil mills will be thoroughly reviewed in the literature. In this study, data and findings from previous studies will be collected, examined and synthesized.